Answer:
Step-by-step explanation:
The solution is in the attached file
Solving by substitution:
y = 4x - 3
2x + 7y = 41
Let us substitute the first equation y = 4x - 3 into the second.
2x + 7y = 41
2x + 7(y = 4x -3) = 41
2x + 7(4x -3) = 41
So that's the third option.
I hope this helps.
Y^2-9^2
(y-9)(y+9)
To see if its right:
y*y+y*9-9*y-9*9
y^2+9y-9y-81
y^2-9^2
Answer:
F(10) = P(x = 10) = 0.3
F(5) = P(x = 5) = 0.4
F(1) = P(x = 1) = 0.3
Step-by-step explanation:
Given the following :
Probability estimates given:
Very successful = 0.3
Moderately successful = 0.4
Unsuccessful = 0.3
Yearly revenue (X) :
Very successful = $10 million
Moderately successful = $5 million
Unsuccessful = $1 million
The probability mass function of X:
f(x) = probability of each valie of x
When x = 10:
F(10) = P(x = 10) = 0.3
When x = 5:
F(5) = P(x = 5) = 0.4
When x = 1:
F(1) = P(x = 1) = 0.3
Answer:
0.00000014972309
Step-by-step explanation:
6/3999=0.00150037509
0.00150037509/10021= 0.00000014972309
hope this helps